EFFECT OF TREATMENTS ON THERMALLY STIMULATED CURRENT AND PHOTOCONDUCTIVITY IN CuInSe2 THIN FILMSEFFECT OF TREATMENTS ON THERMALLY STIMULATED CURRENT AND PHOTOCONDUCTIVITY IN CuInSe2 THIN FILMS (Sciences & Technology. A, exactes sciences, 2003)
CuInSe2 polycrystalline thin films (CIS) have been prepared by the coevaporation method from three boats (Cu, In, Se). “Thermally Stimulated Current” method (TSC) has been used to identify some defect states in the material. Photocurrent versus 1000/T characteristics have also been carried out. In this paper, we discuss the effects of O2 and H2 plasmas on (TSC) and photoconductivity in p and n type CuInSe2 thin films. In fact, strong (TSC) has been exhibited for these films at temperatures from 80 to 500K using coplanar configuration with thermal evaporated Cr-Ag contacts while a stability of photocurrent has been observed. Exposure to O2 and H2 plasmas modified this behaviour leading to a change of (TSC) way and appearing of the thermal “Quenching” in photoconductivity spectra.